2013
DOI: 10.1177/1076029613483169
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Angiographic Thrombus Burden in Patients With ST-Segment Elevation Myocardial Infarction

Abstract: Present study results demonstrated that high thrombus burden in patients with STEMI was associated with impaired postprocedural epicardial and myocardial perfusion and higher no reflow and distal embolization; and increased RDW values were independent predictors of coronary thrombus burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 21 publications
2
45
1
4
Order By: Relevance
“…Previous studies have demonstrated that age, diabetes mellitus, red cell distribution, intrinsic platelet reactivity, increased mean platelet volume at admission, increased epicardial adipose tissue thickness, bilirubin Levels, monocyte to HDL cholesterol ratio, SYNTAX score and absence of pre‐infarction angina were independent predictors of TB in patients with STEMI . In this cohort, we did not observe an association between the above mentioned predictors and intracoronary TB in these young adults with STEMI.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Previous studies have demonstrated that age, diabetes mellitus, red cell distribution, intrinsic platelet reactivity, increased mean platelet volume at admission, increased epicardial adipose tissue thickness, bilirubin Levels, monocyte to HDL cholesterol ratio, SYNTAX score and absence of pre‐infarction angina were independent predictors of TB in patients with STEMI . In this cohort, we did not observe an association between the above mentioned predictors and intracoronary TB in these young adults with STEMI.…”
Section: Discussioncontrasting
confidence: 73%
“…Previous studies showed that the extent of coronary TB in patients with STEMI was associated with age, diabetes mellitus, red cell distribution, intrinsic platelet reactivity, higher troponin and leukocyte concentrations, increased mean platelet volume, increased epicardial adipose tissue thickness, bilirubin levels, monocyte to high‐density lipoprotein (HDL) cholesterol ratio and absence of pre‐infarction angina . It is to note that the study cohorts of above mentioned observations refereed mostly patient population aged >45‐years old.…”
Section: Introductionmentioning
confidence: 99%
“…Angiographic coronary thrombus burden was scored based on TIMI thrombus grade. Patients with a thrombus burden of grade 4 or 5 were defined as having high thrombus burden, ad patients with thrombus burden < grade 4 was defined as having low thrombus burden (11). No thrombolytic therapy or thrombectomy was administered before or after the procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Prediction of thrombus burden and composition, as well as plaque volume and composition, before the procedure in patients with STEMI undergoing PPCI, may contribute to optimize percutaneous treatment of these highly thrombotic lesions, guiding utilization of pharmacological agents or interventional strategies, in order to reduce thrombus burden and improve both epicardial and myocardial perfusion. Grade Ⅲ ischemia on electrocardiogram, defined as distortion of the terminal portion of the QRS complex, and red cell distribution width (RDW), a marker of variation in the size of circulating red cells routinely reported as a part of blood count analysis, were shown to be independent predictors of coronary thrombus burden in STEMI patients undergoing PPCI, and to be associated with angiographic no-reflow and impaired epicardial and myocardial perfusion [39][40][41] . Probably, also the evaluation of thrombus burden using, not only coronary angiography, but also intravascular imaging modalities, such as ultrasound, optical coherence tomography or virtual histology, may provide important informations about the amount and composition of coronary thrombi, thus facilitating the choice of treatment strategies.…”
Section: Prognostic Significance Of Angiographically Detected Coronarmentioning
confidence: 99%